2018
DOI: 10.1161/atvbaha.117.310079
|View full text |Cite
|
Sign up to set email alerts
|

DKK3 (Dickkopf 3) Alters Atherosclerotic Plaque Phenotype Involving Vascular Progenitor and Fibroblast Differentiation Into Smooth Muscle Cells

Abstract: Cumulatively, we provide the first evidence that DKK3 is a potent SMC differentiation factor, which might have a therapeutic effect in reducing intraplaque hemorrhage related to atherosclerotic plaque phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 42 publications
3
54
1
1
Order By: Relevance
“…DKK3 is strongly expressed in endothelial, smooth muscle cells, and platelets 21‐22,27. Consistent with this finding, DKK3 expression partially co‐localized with cavernous endothelial cells.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…DKK3 is strongly expressed in endothelial, smooth muscle cells, and platelets 21‐22,27. Consistent with this finding, DKK3 expression partially co‐localized with cavernous endothelial cells.…”
Section: Discussionsupporting
confidence: 76%
“…In a prospective population‐based study, plasma DKK3 concentrations showed an inverse correlation with intima‐media thickness of common carotid artery 21. Serum DKK3 levels were lower in patients with symptoms of unstable angina than those with stable angina 22. These findings suggest angiogenic and vascular protective functions of DKK3.…”
Section: Introductionmentioning
confidence: 91%
“…The differentiation of Sca-1 + cells into SMCs or ECs may participate in endothelial layer regeneration 122 and promote atherosclerotic plaque stability. 123 Furthermore, this capacity of Sca-1 + cells could find a useful application of in tissue engineering, such as artificial vessel generation. 124 …”
Section: Vascular Resident Stem Cells In Adultsmentioning
confidence: 99%
“…Another study showed that the absence of DKK3 leads to vulnerable atherosclerotic plaques because of reduced numbers of SMCs and matrix protein deposition, as well as increased hemorrhage and macrophage infiltration. 123 Furthermore, the in vitro studies revealed that DKK3 can induce the differentiation of Sca-1 + vascular progenitors into SMCs, via activation of the TGFβ/ATF6 (activating transcription factor) and Wnt signaling pathways. Wang et al 174 also demonstrated that DKK3 can stimulate murine stem cell differentiation into SMCs by activating ATF6 and promoting myocardin expression.…”
Section: Vascular Progenitor Cells In Arteriosclerosismentioning
confidence: 99%
“…In myocardial infarction conditions, the absence of DKK3 increased the mortality and infarct size, along with an increase in cardiomyocyte apoptosis and inflammation [9]. As a smooth muscle cell differentiation factor, the absence of DKK3 also leads to atherosclerotic plaque formation by increasing vascular inflammation [23]. The inhibition of inflammation in myocardial infarction might be associated with the regulation of the NF-κB pathway, which is also a cardioprotective regulator of pathological cardiac hypertrophy.…”
Section: Introductionmentioning
confidence: 99%